Molecular Identification of Decay Fungi in Xylem of Yellow Meranti (Shorea gibbosa) Canker - Erwin Erwin; Shuhei Takemoto; Yuji Imamura (Wood Research Journal, 2010)
By molecular technique, identification of decay fungi isolated from decayed xylem of the tree canker of yellow meranti (Shorea gibbosa) have been carried out.  In this molecular identification, the ITS (Internal Transcribed Spacers) region of rDNA of fungal isolates were amplified and sequenced. The DNA sequence for each fungus was aligned with that of known species in the ITS region of rDNA database for fungi. By phylogenetic analysis based on the sequences of the ITS region of rDNA, a basidiomycete fungi isolated from decayed xylem of yellow meranti was identified as Phlebia  brevispora. The presence of ascomycete fungi on the decayed xylem samples was also detected and identified as Aspergillus nomius, Phlogicylindrium sp., Hypocrea rufa, Hypocrea lixii, Talaromyces sp., and Trichoderma virens.